Association between maternal sugar-sweetened beverage consumption and the social-emotional development of child before 1 year old: A prospective cohort study - Gao, Rui; Liu, Xuemei; Li, Xiuxiu; Zhang, Yuanxing; Wei, Min; Sun, Peng; Zhang, Jianan; Cai, Li (Frontiers in Nutrition, 2022)
Background: Excessive consumption of sugar-sweetened beverages (SSBs) has become an international concerned public health issue. The adverse effects of sugary beverage consumption on both mother and child during pregnancy continue to be found. However, evidence about maternal SSBs consumption and social-emotional development of children is lacking. Methods: Based on the Shenzhen Birth Cohort Study (loss rate: 10.97%), we included 985 mother-infant pairs from 2018 to 2022. All mothers had a singleton live birth without hypertension, diabetes, tumor and serious immune system disease before pregnancy were included. We used chart of frequency distribution to show maternal SSBs consumption, including non-diet soda, tea drinks (not 100% tea), fruit drinks, sugar-sweetened coffee-milk tea-cocoa drinks, and total SSBs. Multivariate logistic regression model was used to estimate the odds ratios of the potential delay on social-emotional development at child ages 6 and 12 months for maternal SSBs consumption. Results: Among the mothers, 728 (73.91%) drank SSBs <1 time per week, 194 (19.70%) drank SSBs 1-2 times per week, 43 (4.37%) drank SSBs 3-4 times per week, and 20 (2.03%) drank SSBs 5 or more times per week. Mothers who drank SSBs 5 or more times per week during pregnancy had an increased risk of potential delay on social-emotional development in children aged 12 months compared with mothers who drank less than 1 time per week [odds ratio: 3.08 (1.13-8.39)]. Regarding the specific kinds of SSBs, we found that tea drinks (not 100% tea) was positively associated with potential delay on social-emotional development in children aged 6 months. Conclusion: Nearly 3/4 mothers consume almost no SSBs during pregnancy. High SSBs intake during pregnancy was associated with an increased risk of the potential delay on social-emotional development of child aged 6 and 12 months.